PEMBERDAYAAN TTG UNTUK MENINGKATKAN PRODUKSI AMPIANG PADA MITRA DI KOTA PANGKALPINANG - somawardi; Zulfitriyanto Zulfitriyanto; Somawardi Somawardi; Embun Ventani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The aim of the Community Service Program for the Ampiang manufacturing group partners in the Selindung Lama sub-district, Gabek District, Pangkalpinang City is to increase production capacity and quality and improve the partner's business management system. The survey results found problems in the fish grinding production process carried out by partners still using the manual method. As a result, partners' production capabilities are limited. In addition, from a business management perspective, partners are still not optimal. The average fish grinding ability of partners is 7-10 kg in 4 hours. From the results of the discussion, the production system was improved by holding a fish grinding machine and marketing management training. Making alternative concepts based on data from literature studies, interviews with partners. The alternative concept chosen as the machine design is assessed based on the results of discussions with partners which are seen in the aspects of frame dimensions, machine height, grinder dimensions, motor power used, machine plate size used. The manufacturing production process is carried out in the Mechanic workshop of the Bangka Belitung State Polytechnic of Manufacturing (Polman Babel). The trial results of the fish grinding machine obtained a very fast time of 10 kg/5 minutes. So that Ampiang's production, which was previously only 15 kg, increased to 45 kg. The business management training that was carried out included small/medium business bookkeeping training, and small industry business management training. As a result, the bookkeeping and marketing process is more focused and orders can be made online.